Estrogen Receptor Complex to Trigger or Delay Estrogen-Induced Apoptosis in Long-Term Estrogen Deprived Breast Cancer - Maximov, Philipp Y.; Fan, Ping; Abderrahman, Balkees; Curpan, Ramona; Jordan, V. Craig (Frontiers in Endocrinology, 2022)
Antiestrogen therapy of breast cancer has been a “gold standard” of treatment of estrogen receptor (ER)-positive breast cancer for decades. Resistance to antiestrogen therapy may develop, however, a vulnerability in long-term estrogen deprived (LTED) breast cancer cells was discovered. LTED breast cancer cells may undergo estrogen-induced apoptosis within a week of treatment with estrogen in vitro. This phenomenon has been also validated in vivo and in the clinic. The molecular ER-mediated mechanism of action of estrogen-induced apoptosis was deciphered, however, the relationship between the structure of estrogenic ligands and the activity of the ER in LTED breast cancer cells remained a mystery until recently. In this review we provide an overview of the structure-activity relationship of various estrogens with different chemical structures and the modulation of estrogen-induced apoptosis in LTED breast cancer cells resistant to antihormone therapy. We provide analysis of evidence gathered over more than a decade of structure-activity relationship studies by our group on the role of the change in the conformation of the estrogen receptor and the biological activities of different classes of estrogens and the receptor as well in LTED breast cancer.